2004
DOI: 10.1139/f04-170
|View full text |Cite
|
Sign up to set email alerts
|

A long-term rusty crayfish (Orconectes rusticus) invasion: dispersal patterns and community change in a north temperate lake

Abstract: Rusty crayfish (Orconectes rusticus) were first observed in Trout Lake, Wisconsin, in 1979 and took 19 years to completely disperse around the littoral zone, advancing at an average rate of 0.68 km·year–1. With the invasion of rusty crayfish, we found that fishes that share prey taxa with crayfish declined in numbers over time, but piscivorous fish species did not change in abundance. Snails declined from >10 000 to <5 snails·m–2 in one of the first invaded areas. Mean abundance of Odonata, Amphipoda, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(209 citation statements)
references
References 44 publications
10
192
3
4
Order By: Relevance
“…These community modifications may thereby potentially affect the results of widely utilised biomonitoring indices and as a result care should be taken when interpreting routine biomonitoring data (i.e water quality, river flow or fine sediment pressures) where non-native / invasive taxa are known to be present (MacNeil et al, 2013, Mathers et al, 2016. This study highlights the value and need for further multi-scale research to fully understand the wider spatial and temporal implications of historic invasions to complement reach scale and mesocosm studies (Wilson et al, 2004;McCarthy et al, 2006). This fundamental knowledge base is needed to inform and underpin management strategies which are aimed at controlling and mitigating the effects of invasive species (Moorhouse et al, 2014).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These community modifications may thereby potentially affect the results of widely utilised biomonitoring indices and as a result care should be taken when interpreting routine biomonitoring data (i.e water quality, river flow or fine sediment pressures) where non-native / invasive taxa are known to be present (MacNeil et al, 2013, Mathers et al, 2016. This study highlights the value and need for further multi-scale research to fully understand the wider spatial and temporal implications of historic invasions to complement reach scale and mesocosm studies (Wilson et al, 2004;McCarthy et al, 2006). This fundamental knowledge base is needed to inform and underpin management strategies which are aimed at controlling and mitigating the effects of invasive species (Moorhouse et al, 2014).…”
Section: Resultsmentioning
confidence: 95%
“…Communities which support abundant populations of taxa susceptible to predation will therefore be more severely affected following invasion events. We are aware of only two other studies which have examined the long-term impact of invasive crayfish on benthic communities thus far (Wilson et al, 2004;McCarthy et al, 2006), however both were focussed on lentic systems in North America over limited spatial scales. Both studies reported significant modifications to benthic community composition with dramatic long term and potentially irreversible effects on the ecosystem evident as a whole.…”
Section: Temporal and Spatial Persistence Of Crayfish Invasion Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigating the impacts of crayfish on other invertebrates is complicated by the fact that such taxa may be differentially affected by crayfish (Usio and Townsend 2000;Twardochleb et al 2013). Crayfish preferentially prey on large soft-bodied invertebrates, such as gastropods (Wilson et al 2004;Bjurström 2009) but are ineffective predators of highly mobile invertebrate grazers, such as mayflies (Bjurström 2009). Therefore the impacts of crayfish on other invertebrates will vary largely depending on the species composition of the affected community, potentially confounding our comparisons between native and invasive crayfish for these variables.…”
Section: Discussionmentioning
confidence: 99%
“…In general, exotic freshwater crayfish are highly successful invaders (Lodge et al 2000) that have been frequently shown to have large impacts on native benthic invertebrate prey (Mccarthy et al 2006;Lodge et al 1994;Wilson et al 2004). Exotic crayfish impacts often arise through their ability to reach high abundances, however, many populations often remain at low densities (Nyström 2002).…”
Section: Introductionmentioning
confidence: 99%